TECHNIQUES FOR IMPROVING LISTENING AND SPEAKING SKILLS IN ENGLISH - Ubaydullayev.B.O’; Maxmudova Madina (TADQIQOTLAR, 2025)
Abstract This article explores evidence-based and pedagogically grounded techniques for enhancing English listening and speaking skills among second language learners. Drawing on insights from influential works by Brown and Yule (1983), Field (2008), and Richards (2008), as well as from practical teaching resources such as the Active Listening series, Jean Yates’s English Conversation, and digital platforms like Speak English with Mr. Duncan and EnglishCentral.com, the paper highlights how communicative competence can be cultivated through targeted strategies.Key themes include the importance of teaching spoken English as a distinct skill set, the use of authentic listening tasks with real-life conversational input, and the implementation of interactive and task-based speaking activities. Process-oriented listening instruction is emphasized as a means to develop learners’ cognitive listening abilities, while speaking fluency is shown to improve through structured exposure to language chunks, idiomatic expressions, and pronunciation practice.The paper also examines the value of technology-enhanced resources and video-based learning for fostering learner autonomy, pronunciation accuracy, and active engagement in language production. Emphasis is placed on integrated skill development, where listening supports speaking and vice versa, through reflective, feedback-informed pedagogy.Overall, the article concludes that a balanced, research-informed approach that combines theoretical foundations with engaging, authentic materials is key to advancing learners’ oral communication abilities in English.